Inter‐ and intra‐rater reliability of blood and cerebrospinal fluid flow quantification by phase‐contrast MRI. Issue 3 (31st January 2013) - Koerte, Inga; Haberl, Caroline; Schmidt, Michael; Pomschar, Andreas; Lee, Sang; Rapp, Petra; Steffinger, Denise; Tain, Rong‐Wen; Alperin, Noam; Ertl‐Wagner, Birgit
<x xml:space="preserve">Abstract</x> Purpose: To evaluate the intra‐ and inter‐rater reliability of the quantification of blood and CSF flow rates by phase contrast MRI. Materials and Methods: Blood and CSF flows in the upper cervical region were imaged with velocity‐encoded cine‐phase contrast using 3T scanners from different manufacturers at two centers. Data of 6 subjects scanned in center A and of 5 subjects in center B were analyzed by six readers at two levels of training. Each data set was analyzed three times in a randomized order for a total of 33 data sets. Intra‐class correlation coefficients (ICC) were calculated for the primary measurements of areas and flow rates through the main cervical arteries, veins and the CSF space, and for secondary parameters derived from the individual flow rates. Results: ICC ranged from 0.80 to 0.96 for the lumen area and from 0.97 to 0.99 for the volumetric flow rate. The ICC for the derived secondary measures ranged from 0.85 to 0.99. Differences due to operator level of training were not statistically significant. Conclusion: High intra‐ and inter‐rater reliability of volumetric flow rate measurements is currently achievable across manufacturers and users' skill levels with a pulsatility based automated lumen segmentation. J. Magn. Reson. Imaging 2013;38:655–662. © 2013 Wiley Periodicals, Inc.